A Multicenter, Double-Blind, Randomized, Placebo-Controlled Trial to Evaluate the Efficacy and Safety of Duliang Soft Capsule in Patients with Chronic Daily Headache. (26th May 2015) - Yu, Shengyuan; Hu, Yueqing; Wan, Qi; Zhou, Jiying; Liu, Xinfeng; Qiao, Xiangyang; Yang, Xiaosu; Feng, Jiachun; Chen, Kangning; Pan, Xiaoping; Yang, Qingwu; Dou, Linsen; et al.
Abstract : Objective . To investigate the efficacy and safety of traditional Chinese medicine Duliang soft capsule (DSC) in prophylactic treatment for patients with chronic daily headache (CDH). Methods . A multicenter, double-blind, randomized, placebo-controlled clinical study was conducted at 18 Chinese clinical centers. The participants received either DSC or placebo for 4 weeks. The primary efficacy measure was headache-free rate (HFR) in a 4-week period between the pretreatment and posttreatment stages. The secondary efficacy measures were the decrease of headache days, the duration of headache attacks, the frequency of analgesic usage, quality of life, disability, and the headache severity (VAS scores). The accompanying symptoms and adverse events were also assessed. Results . Of 584 CDH patients assessed, 468 eligible patients were randomized. 338 patients received DSC, while 111 patients were assigned in the placebo group. Following treatment, there was a 16.56% difference in HFR favoring DSC over placebo (P < 0.01 ). Significant differences were also observed between DSC and placebo groups in the secondary measures. However, no statistical difference was found between the two groups in the associated symptoms. No severe adverse effects were observed in the study. Conclusions . DSC might be an effective and well-tolerated option for the prophylactic treatment of patients with CDH.